Die Verteilung der algebraischen Primzahlen - Urbelis, J. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. Урбялис, Распределение простых алгебраических чиселJ. Urbelis. Pirminių algebrinių skaičių pasiskirstymas